Pengaruh budaya organisasi, lingkungan kerja non fisik dan locus of control terhadap kepuasan kerja karyawan - Mahayasa, I Gede Aryana; Maitarini, Ida Ayu Nadia; Wulandari, Ni Luh Adisti Abiyoga (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2024)
The purpose of this research is to determine the influence of organizational culture, non-physical work environment, and locus of control on the job satisfaction of Yamaha Waja Motor Sentral Gianyar employees. The population and sample in this research were all employees of Yamaha Waja Motor Sentral Giansar, with a total of 42 people. The saturated sampling method was used, where the entire population was used as the research sample. The data collection method used a questionnaire distributed to the respondents. The test techniques used were research instrument tests, classical assumption tests, multiple linear regression analysis, t test and F test. The results obtained in this research are as follows: organizational culture has a positive and significant effect on employee job satisfaction, the non-physical work environment has a positive and significantly on employee job satisfaction, locus of control has a positive and significant effect on employee job satisfaction and the organizational culture of the non-physical work environment and locus of control has a positive and significant effect simultaneously on employee job satisfaction. Suggestions that can be given are that leaders can emphasize their employees to control their attitudes when carrying out work. Keywords: Organizational culture, non-physical work environment, locus of control and employee job satisfaction.